Improving dyeability of modified cotton fabrics by the natural aqueous extract from red cabbage using ultrasonic energy. (10th December 2016) - Ben Ticha, Manel; Haddar, Wafa; Meksi, Nizar; Guesmi, Ahlem; Mhenni, M. Farouk
Highlights: Improved the dyeability of cotton with a natural dye extract. Modification of cotton by cationic agents. Sonicator dyeing of modified cotton with the aqueous extract of red cabbage. Good fastness obtained for the dyed modified cotton. Abstract: The concern regarding sustainable utilization of available resources is growing due to its global importance. In this paper, the dyeability of cotton fabrics with natural colorant extracted from red cabbage was improved by applying cationic groups on cotton fibers. Modification of cotton was carried using acid tannic, Rewin Os, Denitex BC and Sera Fast as cationic agents. The dyeing process was done by ultrasonic energy. The effects of the cationising agent amount, the dye bath pH, the dyeing temperature and duration, on the sonicator dyeing quality were studied. The performances of this process were evaluated by measuring the colour yield (K/S) and the dyeing fastness of the coloured cotton. Besides, modified cotton fibers were characterized by morphology analysis (SEM) and Fourier transform infrared (FTIR) spectra and compared to untreated cotton. Moreover, a two-level full factorial design was employed to optimize the sonicator dyeing process. Mathematical model equation and statistical analysis were derived by computer simulation programming applying the least squares method using Minitab 15. Best dyeing conditions were found to be: 10%, pH 11, 60 min and 100 °C respectively for the Sera Fast amount, dye bath pH, dyeing duration and temperature.